Does high-intensity work intensify the imbalance between health and income? Evidence from rural China - Zhao, Mao; Xiong, Yu; Wang, MiaoJie; Zhang, YuHang; Cao, YaJing (Frontiers in Public Health, 2025)
Understanding the interplay between health and income among rural populations is essential for achieving sustainable development and reducing global inequalities. This paper evaluated the health-income coupling coordination degree (CCD) among farmers by utilizing data from the 2018 China Labor Force Dynamics Survey. It analyzed the impact of high-intensity work on the CCD among farmers by using the endogenous switching probit model (ESP). Additionally, this paper investigated the individual variations in the impact effect. This paper reveals that high-intensity work has a detrimental impact on the CCD among farmers. Farmers engaged in high-intensity work have an 8.527% higher probability of experiencing imbalanced CCD than those with low-intensity work. Furthermore, the adverse effect of high-intensity work on the CCD is more pronounced among farmers working in a different location than those working locally. These findings hold significance for assisting developing countries worldwide in achieving prosperity for farmers and rural development.